2007
DOI: 10.1093/ndt/gfm582
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting long-term survival of tunnelled haemodialysis catheters a prospective audit of 812 tunnelled catheters

Abstract: Clinicians need accurate data regarding catheter survival, mode of insertion and design, to inform practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 25 publications
2
63
2
1
Order By: Relevance
“…The quality of hemodialysis is often associated with adequate blood flow rates, which are improved when the tip is positioned in the right atrium, but many clinicians still have the fear that right atrium thrombus or arrhythmia would be developed. Some data adversely associate left-sided access with catheter durability [7] although without mentioning the exact reason. The aim of this study was to examine the impact of different catheter tip positions on catheter duration, dysfunction, infection, and quality of hemodialysis and possible differences between the access site laterality in jugular-tunneled hemodialysis catheters.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of hemodialysis is often associated with adequate blood flow rates, which are improved when the tip is positioned in the right atrium, but many clinicians still have the fear that right atrium thrombus or arrhythmia would be developed. Some data adversely associate left-sided access with catheter durability [7] although without mentioning the exact reason. The aim of this study was to examine the impact of different catheter tip positions on catheter duration, dysfunction, infection, and quality of hemodialysis and possible differences between the access site laterality in jugular-tunneled hemodialysis catheters.…”
Section: Introductionmentioning
confidence: 99%
“…The type of infections comprise exit-site infection, tunnel infection, and bacteremia. Despite the fact that exit-site and tunnel infections are the most common complications, 3,4 catheter-related bacteremia (CRB) is the most serious one, representing a barrier to long-term catheter use and emerging as a significant cause of morbidity and mortality. 5 Some studies have demonstrated that in patients using a hemodialysis catheter, the risk of death is 1.5-to threefold higher when compared with patients with a primary arteriovenous fistula.…”
mentioning
confidence: 99%
“…When the use of the IJV is not feasible, other venous routes such as the EJV or femoral vein for catheter placement are usually selected. When conventional venous routes are exhausted, unusual venous access routes such as the brachiocephalic vein, and translumbar and transhepatic routes have been attempted by interventional radiologists with a relatively higher complication rate (5)(6)(7)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the left IJV approach had relatively higher rates of stenosis and thrombosis compared to the right IJV approach (1,13,14,30,31). Our thinking is that the catheter passes through the narrow space between the sternum and aortic arch, and can cause injury or may induce stenosis by close approximation of the catheter tip to the wall of the superior vena cava.…”
Section: Discussionmentioning
confidence: 99%